Analyzing Building Height Restrictions: Predicted Impacts, Welfare Costs, and a Case Study of Bangalore, India - Bertaud, Alain (World Bank, Washington, D.C., 2013)
The authors analyze the effects of building height restrictions, providing a concrete welfare cost estimate for the city of Bangalore, India. Relying on several theoretical results, their analysis shows that the welfare cost imposed on its residents by Bangalore's building height restriction ranges between 3 and 6 percent of household consumption. This burden represents a significant share of individual resources, and its presence may push many marginal households into poverty.